Alteration of proteins upon high-pressure processing treatment - Yildiz, Gulcin; Yıldız, Gökçen (Elsevier, 2025)
High-pressure processing (HPP) is an innovative nonthermal technology used in the food industry to enhance food safety, extend shelf life, and preserve sensory and nutritional qualities. This chapter explores the alterations in protein structure and functionality resulting from HPP. Proteins are sensitive to high pressure, which can lead to changes in their conformation, aggregation, and engagement with other food components. The extent and nature of these alterations depend on various factors, including pressure levels, treatment duration, pH, the specific protein's type and structure, and presence of other food components. The chapter investigates the effects of HPP on protein denaturation, unfolding, and aggregation, as well as the resultant impacts on protein solubility, emulsifying abilities, foaming characteristics, gelation, rheological features, and water/oil holding ability. Additionally, it examines how HPP affects the enzymatic activity of proteins, with implications for food safety and nutrition. The findings demonstrate that HPP can be tailored to achieve desired modifications in protein properties, offering potential applications in developing novel food products and enhancing the quality of existing ones. The chapter contributes to a more detailed exploration of the molecular dynamics influencing protein alteration during HPP, paving the way for future research and applications in food research and technology. © 2025 Elsevier Inc. All rights reserved.
Keywords: denaturation; functionality; High-pressure processing; modification; proteins